Burkina Faso : Sixth Review Under the Poverty Reduction and Growth Facility, and Requests for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2002)
This paper assesses the Sixth Review Under the Poverty Reduction and Growth Facility (PRGF) and Requests for Waiver of Performance Criteria for Burkina Faso. The implementation of the PRGF-supported program remains largely satisfactory, with all but one of the quantitative benchmarks and indicators for end-March 2002 met, and all but two of the quantitative performance criteria, benchmarks, and indicators met at end-June 2002. The performance criterion on total net budget financing and the indicator on the ceiling on current government expenditure were not met at end-June.